Numerical study and topology optimization of vibration isolation support structures. (15th August 2022) - Zhao, Haojiang; Feng, Yang; Li, Wei; Xue, Chuang
Highlights: Vibration isolation support structures are obtained by topological optimization. Maze algorithm is used to avoid invalid operation in optimization process of GA. The coarse and fine mesh generation strategy improves the operation efficiency. Two different symmetry constraints in the microstructures are analyzed. Bandgaps with different mechanisms are found by multi-objective optimization. Abstract: Lightweight design and harmful vibration isolation of supporting structures are the most common design contents in practical engineering, but they are often difficult to be considered together. Phononic crystals have the characteristics of elastic wave bandgaps, which can effectively isolate the vibration within the bandgap frequency range. The integrated coupling design of vibration isolation and structure support by topology optimization is studied in order to make the obtained macro structure with periodic characteristics have both high support structure stiffness and lower frequency vibration isolation bandgaps. Taking a two-dimensional cantilever beam with multiple periodic substructures in the length direction for example, the finite element method and an improved multi-objective genetic algorithm are used to realize the topology iterative change of the substructure mesh, the solution of the substructure band structure and the natural frequency of the cantilever beam. Maze algorithm is used to avoid invalid operation in optimization process and the mesh generation strategy combining coarse mesh and fine mesh is taken to improve the operation efficiency. Two optimization objective functions reflecting the overall support stiffness and relative bandgap width of the cantilever beam are set. The topology design of the substructure with transverse symmetry constraints and bisymmetric constraints are carried out, respectively. The topology optimized structures with bandgaps of different mechanisms are obtained from the Pareto front of the numerical results. Graphical abstract: Image, graphical abstract